taste Aversion Motivated by Stomach Distention - Bowman, Thomas (My University, 1976)
Previous research has indicated two distinctive characteristics of flavour-aversion learning in rats: (1) rats very readily associate flavors with an internal malaise (toxicosis) , as evidenced by their subsequent aversion to the flavor, but they do not readily associate flafors with peripherally-applied electric shock. In contrast, rats readily associate auditory and visual stimuli with shock but not with toxicosis; (2) rats associate flavors with a subsequent toxicosis even when the gustatory stimulus is removed hours prior to onset of toxicosis. However, associations are formed between audio/visual cues and shock only if the offset of the signal does not precede onset of shock by more than one or two minutes. It has been suggested that the unique features of flavour-aversionn learning result from the fact that toxicosis is primarily a visceral experience while shock is applied to somesthetic receptors. However, toxicosis differs from shock along a number of dimensions in addition to receptor site. Most notably, toxicosis typically rises to a peak intensity over a period of many minutes and lasts for hours while shock is usually applied with a rapid onset (milliseconds) and short duration (seconds or milliseconds). Inasmuch as aversion learning experiments have confounded the receptor site of the aversive stimulus with its distinctive temporal features, it is not clear whether receptor site or temporal features is the functionally important characteristic of toxicosis as an aversive stimulus in the taste-aversion learning preparation. To determine the role played by the temporal features of the aversive stimulus in taste-aversion learning, rats were prepared with a stomach balloon and stomach balloon inflation was paired with ingestion of a flavored solution. In contrast to toxicosis, the onset/offset rate and duration of balloon inflation may be directly manipulated thus permitting application of a relatively discrete internal stimulus (in comparison to toxicosis) to visceral receptors. Experiments presented here found: (a) rats associated a flavor with a stomach balloon inflation as indicated by an aversion to the flavor during a two-solution preference test. In contrast to toxicosis, the stomach balloon inflation had a rapid onset (seconds) and short duration (minutes). Control groups demonstrated that the rapid onset, short duration balloon inflation did not produce the long lasting malaise characteristic of toxicosis. (b) Rats associated a flavor with a rapid onset, short duration balloon inflation even when exposure to the flavor was terminated many minutes prior to onset of balloon inflation. (c) Rats readily associated a flavor with balloon inflation but not with shock, and an auditory stimulus with shock but not with balloon inflation, even though balloon inflation and shock were equated in terms of their temporal parameters. These findings clearly indicate that the very slow onset and long duration characteristics of toxicosis are not the functionally important features of toxicosis as the aversive stimulus in the taste-aversion learning preparation. Furthermore, the unique temporal features of toxicosis and shock do not appear responsible for the distinctive characteristics of flavor-aversion learning in rats.
Keywords: taste aversion; distention; stomach